2007
DOI: 10.1128/jb.01547-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diverse Archaeal Proteins with Class III Signal Peptides Cleaved by Distinct Archaeal Prepilin Peptidases

Abstract: Most secreted archaeal proteins are targeted to the membrane via a tripartite signal composed of a charged N terminus and a hydrophobic domain, followed by a signal peptidase-processing site. Signal peptides of archaeal flagellins, similar to class III signal peptides of bacterial type IV pilins, are distinct in that their processing sites precede the hydrophobic domain, which is crucial for assembly of these extracytoplasmic structures. To identify the complement of archaeal proteins with class III signal seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
242
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(247 citation statements)
references
References 44 publications
4
242
0
1
Order By: Relevance
“…Sso3138, Sso3139, and Sso3140 were predicted to be primarily located extracellularly (see Fig. S1 in the supplemental material), correlating with a previous prediction of the presence of class III signal peptides at their N termini (26). Among these, Sso3140 was confirmed to be a membrane-associated protein in a proteomics study (27).…”
Section: Sirv2 Entry In Sulfolobussupporting
confidence: 55%
“…Sso3138, Sso3139, and Sso3140 were predicted to be primarily located extracellularly (see Fig. S1 in the supplemental material), correlating with a previous prediction of the presence of class III signal peptides at their N termini (26). Among these, Sso3140 was confirmed to be a membrane-associated protein in a proteomics study (27).…”
Section: Sirv2 Entry In Sulfolobussupporting
confidence: 55%
“…Genome sequence analysis in search of type IV pilin-like signal peptides led to the identification of a number of type IV pilin-like genes, MMP0233 (encoding a protein with a predicted molecular mass of 14.4 kDa, with the signal peptide), MMP0236 (encoding a protein with a predicted molecular mass of 14.2 kDa, with the signal peptide), and MMP0237 (encoding a protein with a predicted molecular mass of 17.3 kDa, with the signal peptide), in a single gene cluster (58). In the cases of MMP0233 and MMP0237, it was also previously demonstrated that both proteins were processed by the type IV prepilin peptidase homologue EppA found in the same gene cluster, further supporting their assignment as type IV pilins (58).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has been presented that in Haloferax volcanii, the PibD equivalent also processes flagellins and pilin-like proteins (65). However, in M. maripaludis, there is a dedicated second peptidase, EppA, for pilin processing that is separate from the flagellin-processing enzyme FlaK (58). In S. solfataricus, transcription of the pilus locus is strongly upregulated, with the number of pili on the surface of the cells greatly enhanced, upon treatment of cells with UV light (26)(27)(28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1), denoted "type III" (379) to distinguish it from the type I (recognized by signal peptidase I) and type II (characteristic of lipoproteins) signal sequences. Canonical type I and type II signal sequences are cleaved at the exterior of the cytoplasmic membrane, C-terminal to a stretch of hydrophobic residues.…”
Section: The Signature Type III Signal Sequencementioning
confidence: 99%